“Breaking Up Can Be So Hard to Do”: Communication Strategies to Disengage from Male Same-Sex Romantic Relationships between Thais and Non-Thais - Khumruk, Parinya; Rimkeeratikul, Sucharat (Asia Social Issues, 2023)
Intimate relationships among male same-sex have been accepted and more received significant attention recently, Resulting in emerging of them from the shadows of society. However, unfortunately, these relationships frequently end in breakups. As a result, this study was aimed to (1) examine the communicative strategies used to disengage from male same-sex relationships, (2) explore the elements contributing to the choice of breakup tactics, and (3) investigate the effects of the disengagement strategies on the post-breakup relationship status. Interviews were used to elicit the participants’ previous relationships. Five male participants who dated a male were selected using the purposive sampling method, and semi-structured interviews were conducted to obtain the data. The adaptation of Baxter’s disengagement tactics served as the framework to describe the communication styles of Thai disengagers during the breakdown of the relationship with non-Thai partners. The findings revealed that the degree of intimacy and the culture of the disengagers influenced the selection of disengagement tactics. Moreover, the length of the relationship and the usage of breakup strategies were found to determine the post-breakup relationship status. As for the implications, the study may enable individuals to select the most appropriate strategies if a breakup is necessary.